A New Perspective on Residential Building Ventilation from the Point of View of Achieving the Desired Indoor Air Quality using Different Ventilation Systems - Straková Zuzana; Marková Júlia (Slovak Journal of Civil Engineering, 2023)
The case study analyses a specifically described situation from the present and a summary of events from the past, finds alternative solutions, and decides on one of them. The target of such a detailed analysis was a concrete apartment building, which was still in the project phase; the efforts to change its proposed air conditioning system to a more energy-efficient one are the subject of the case study. Apartment buildings with modern technology installed in terms of sanitary equipment, heating, and simple methods of ventilation and cooling do not constitute part of the project.